La alienación cultural y el funcionamiento familiar de los estudiantes de primero de bachillerato del colegio Vilcabamba, de la parroquia Vilcabamba, de la provincia de Loja, periodo 2013 – 2014 - Ochoa Romero, Ángel Alcides (2014)
The present investigation, code-named: THE ALIENACIÓN CULTURAL AND FAMILY FUNCTIONING OF THE FIRST-YEAR STUDENTS AT THE COLLEGE BACCALAUREATE VILCABAMBA, THE PARISH OF VILCABAMBA, IN THE PROVINCE OF LOJA, PERIOD 2013 - 2014 , taking as general objective: to analyze the influence of cultural alienation on family functioning of families of adolescents in question; the research was descriptive, for the development of the same were applied the following methods, scientific, statistical, analytic-synthetic, descriptive and bibliographical. The instruments were: a structured survey by 8 questions relating to the two variables, and the test of perception of family functioning FF-SIL. . The study population was 307 students, of this population were 92 students in the sample. One of the most salient results are; the type of cultural alienation present in adolescents is the consumerist with the 52 %, and the families are mostly moderately functional in a 54.35 %. It was concluded that the type of cultural alienation evidenced in adolescents is the consumerist; families are in a greater percentage moderately functional, and that the family functionality if it influences for the cultural alienation in adolescents.